2007
DOI: 10.1002/bmb.40
|View full text |Cite
|
Sign up to set email alerts
|

A case‐based approach increases student learning outcomes and comprehension of cellular respiration concepts

Abstract: This study investigated student learning outcomes using a case-based approach focused on cellular respiration. Students who used the case study, relative to students who did not use the case study, exhibited a significantly greater learning gain, and demonstrated use of higher-order thinking skills. Preliminary data indicate that after engaging with the case study, students were more likely to answer a question addressing misconceptions about cellular respiration correctly when compared with students who did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 16 publications
4
32
1
3
Order By: Relevance
“…The lecturer who implemented case-based learning improved students' thinking ability as much as 40% using up to date cases (Hasslöf et al, 2014). Case-based learning improves the content retention and decreases misconception (Rybarczyk et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lecturer who implemented case-based learning improved students' thinking ability as much as 40% using up to date cases (Hasslöf et al, 2014). Case-based learning improves the content retention and decreases misconception (Rybarczyk et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…We use the term model of teaching refers to the explanation Arends (2012). The socio-biological case-based learning is a pedagogical method that uses cases and issues in society related to the concept of biological science as a foundation of inquiry and scientific thinking (Rybarczyk et al, 2007). The socio-biological case-based learning provides students practice inquiry activities, highorder thinking skills, and collaborative skills in studying biological processes in the relevant real world context.…”
Section: Introductionmentioning
confidence: 99%
“…Case studies done in collaborative settings have been shown to decrease failure rates (Cliff and Wright 1996;Freeman et al 2007;Hartfield 2010) and to facilitate learning at higher levels of Bloom's taxonomy (Bloom 1956), more than lecturing alone (Davies 2004;Fardilha et al 2010;Perin 2011;Rybarczyk et al 2007). In most variants of CBL, students, in small groups, are challenged to listen and to make trade-offs with one another while confronting their own assumptions and values related to a topic (Chaplin 2009).…”
Section: What Is It?mentioning
confidence: 97%
“…While Wood and Anderson had done study on Case-based Learning and revealed that the case-based learning method could improve teachers' skill in giving question effectively because cases could give opportunity for the teachers to think based on the reality [4]. In addition, Rybarczyk et al had stated that the use of case-based learning was very comprehensive with other learning objectives such as minimalize students' understanding and improving students' learning motivation [5].…”
Section: Diagram 1 Cycles On Cased-based Learningmentioning
confidence: 99%